Fiber web product and method of making the same
Patent Information
- Application Number
- CN202280003854.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-22
- Filing Date
- 2022-06-14
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-06-14
AI Technical Summary
[0048]根据本发明,能够提供一种纤维幅材制品,其通过将纸浆纤维的种类、与药液配合的保湿成分、水分、油性成分、植物性粉体的量设为特定范围内,纤维幅材表面的平滑的起毛感、柔软度、湿润感、无发粘等肌肤触感性优异,并且不配合粘接成分而粉体、纸浆纤维等粉尘的产生、脱落较少。此外,能够得到保有充分的强度并且实际使用性优异、最适合卫生用途、家庭用途的纤维幅材制品。
Smart Images

Figure CN116348020B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a fiber web product obtained by impregnating a fiber web with a pharmaceutical solution containing a given component, and a method for manufacturing the same. The fiber web product is a fiber web product for hygiene and household use, such as facial tissue, toilet paper, and towel paper. Background Technology
[0002] As background technology, for example, Patent Document 1 discloses a highly moisturizing fiber web product that has a moist feel by impregnating the fiber web with a moisturizing agent in order to improve softness and skin feel.
[0003] Furthermore, Patent Document 2 discloses a fiber web product that improves its oil absorption, refreshing feel, and softness by containing powder and moisturizing ingredients composed of inorganic or organic substances or mixtures thereof.
[0004] Furthermore, Patent Document 3 discloses a medicinal paper obtained by containing a liquid containing various powders with different average particle sizes in the base paper, and Patent Document 4 discloses a medicinal paper obtained by containing talc powder, paper softener and moisturizing ingredients of a given particle size in the base paper. Both types of paper aim to improve the refreshing feel, smoothness and softness.
[0005] Furthermore, Patent Document 5 describes a method for improving the softness and fluffiness of crepe-textured sanitary paper by physically atomizing the pulp fibers on the surface. As a physical method, it discloses methods such as peeling the pulp fibers by cutting or scraping them with multiple needles arranged on the outer circumference of a roller.
[0006] [Existing Technical Documents]
[0007] [Patent Literature]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 5-156596
[0009] [Patent Document 2] Japanese Patent Application Publication No. 2001-11790
[0010] [Patent Document 3] Japanese Patent Application Publication No. 2007-204868
[0011] [Patent Document 4] Japanese Patent Application Publication No. 2008-80027
[0012] [Patent Document 5] Japanese Patent Application Publication No. 2003-342899 Summary of the Invention
[0013] [The technical problem solved by the invention]
[0014] Although the fiber web product of Patent Document 1 has a high level of moisture, its surface smoothness is not sufficient. As a fiber web product for sensitive skin, it needs further improvement.
[0015] According to the fiber web product of Patent Document 2, the surface cleanliness and smoothness are improved, but the powder shedding inhibition effect is insufficient when no adhesive components are included, and the fuzzing of pulp fibers is not mentioned.
[0016] Patent documents 3 and 4 do not disclose knowledge related to powder shedding inhibition or pulp fiber fuzzing.
[0017] Furthermore, in the sanitary paper of Patent Document 5, in the process of physically and forcibly generating the nap of pulp fibers, in addition to requiring mechanical devices such as rollers and their driving mechanisms, there is also a problem that paper dust is easily generated due to the pulp fibers breaking to a certain extent.
[0018] Therefore, the problem solved by the present invention is to provide a fiber web product and a method thereof that, by simply impregnating the fiber web with a solution containing specific moisturizing ingredients, water, oily ingredients and plant-based powders in a given ratio, can naturally generate a thick, napped texture without the use of any machinery or devices, and has excellent softness, moisture and other skin-touch properties.
[0019] Furthermore, another problem solved by the present invention is to provide a fiber web product capable of suppressing the generation of dust such as powder and pulp fibers, and a method for manufacturing the same.
[0020] [Technical means to solve the problem]
[0021] To solve the aforementioned problem, the fiber web product of the present invention is characterized in that: for a fiber web containing broadleaf pulp, it is impregnated with a medicinal solution containing moisturizing ingredients, moisture, oily ingredients, and plant powders.
[0022] In the fiber web of this invention, it is preferable to use dry crepe paper, which is formed with a crepe texture by a doctor blade on a paper machine during papermaking. This dry crepe paper contains hardwood pulp as wood fiber, and may also contain one or more of the following, in addition to softwood pulp as other wood fibers: non-wood plant fibers (hemp, bast fibers, cotton, kenaf, etc.), man-made fibers, and synthetic fibers (nylon, polyethylene, polyester, polypropylene, etc.).
[0023] The pulp fibers preferably include wood fibers plasticized by water and non-wood plant fibers, and preferably include at least 80% by weight of hardwood pulp and softwood pulp as wood fibers relative to the total fiber web. In particular, it is preferable that the pulp contains at least 50% by weight of hardwood pulp relative to the fiber web, more preferably at least 70% by weight, more preferably at least 80% by weight, and most preferably at least 90% by weight.
[0024] Compared to softwood pulp, hardwood pulp has shorter and finer fibers, resulting in fewer hydrogen bonds and a smaller bonding area between the fibers. The presence of moisturizing components, water, oils, and plant-based powders in the pulp solution makes the bonds between the pulp fibers easier to separate, leading to fiber fuzzing on the fiber web surface. Furthermore, hardwood pulp has a higher fiber count per unit weight compared to softwood pulp, resulting in a greater number of fuzzy pulp fibers.
[0025] For these reasons, it is desirable to have as much hardwood pulp as possible in the fiber web.
[0026] The moisturizing components in the liquid of this invention can absorb moisture from the surrounding environment, increase the moisture content of the pulp fibers, and make the pulp fibers soft.
[0027] Examples of moisturizing ingredients include: glycerol, diglycerol, polyglycerol, polyethylene glycol (with an average molecular weight of 200 or more and less than 1000), propylene glycol, 1,3-butanediol, ethylene glycol, diethylene glycol and other polyols, sorbitol, xylitol, erythritol, mannitol, lactitol, oligosaccharide alcohols, maltitol, reduced starch hydrolysate and other sugar alcohols, fructose, glucose, oligosaccharides, trehalose, glycine betaine, pyrrolidone carboxylic acid, pyrrolidone carboxylate, sodium lactate, etc.
[0028] Among them, glycerol is suitable as a moisturizing ingredient due to its high hygroscopicity, and sorbitol has excellent water retention properties, so when used in combination with glycerol, the stability of water content relative to changes in the surrounding environment is increased.
[0029] The moisture contained in the fiber web product of the present invention includes moisture from the pharmaceutical solution and moisture absorbed from the surrounding environment through moisturizing ingredients, etc. The amount of moisture absorbed from the surrounding environment varies depending on the hygroscopicity of the moisturizing ingredients and the humidity of the surrounding environment. Therefore, it is preferable to anticipate the amount of moisture absorbed from the surrounding environment and determine and adjust the amount of moisture in the pharmaceutical solution accordingly.
[0030] The oily components in the solution smooth the surface of the pulp and transfer to the skin, giving it a smooth feel. Furthermore, the adhesive properties of the oily components prevent the shedding of dust containing plant-based powders, pulp fibers, etc.
[0031] The oily component is preferably formulated by emulsifying it into an oil-in-water emulsion using surfactants in water and moisturizing ingredients.
[0032] Examples of this oily component include: liquid paraffin, solid paraffin, hydrocarbons such as squalane, vegetable oils such as olive oil, camellia oil, castor oil, and soybean oil, fatty acids such as stearic acid, palmitic acid, myristic acid, and lauric acid, waxes such as beeswax, carnauba wax, and lanolin, higher alcohols such as lauryl alcohol, cetyl alcohol, stearyl alcohol, and oleyl alcohol, and esters such as isopropyl myristate and isopropyl palmitate. Among these oily components, hydrocarbons and vegetable oils are preferred, saturated hydrocarbons that are not easily oxidized are more preferred, and hydrocarbons that are liquid at 23°C are most preferred.
[0033] As surfactants, suitable nonionic surfactants such as sucrose fatty acid esters, sorbitan fatty acid esters, glycerol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene fatty acid esters, and polyoxyethylene sorbitan fatty acid esters, as well as anionic surfactants such as fatty acid salts, alkylbenzene sulfonates, and polyoxyethylene alkyl ether sulfates, are suitable.
[0034] The powder in the solution is preferably a plant-based powder with a high affinity for water, which can promote napping by entering (intervening) between pulp fibers while producing a smooth feel.
[0035] Examples of plant-based powders include wood flour, bamboo flour, plant fiber powder, cellulose powder, and starches. These plant-based powders are preferably spherical or polyhedral in shape, and starches are particularly preferred from the viewpoints of ease of handling and safety. Among these starches, corn starch, potato starch, rice flour, and wheat flour are preferred, with corn starch being the most preferred.
[0036] The average particle size of the plant-based powder is preferably 2 to 50 μm, more preferably 5 to 30 μm.
[0037] It should be noted that when starch is heated in the presence of moisture, it gelatinizes and the particles dissolve, thus losing their powder form. Furthermore, the gelatinized starch forms hydrogen bonds between the pulp fibers, increasing the strength of the fiber web products to a necessary level, thereby making the products harder.
[0038] Therefore, when starch is used as a plant-based powder in this invention, it is preferable to maintain the temperature of the emulsion containing moisturizing ingredients, water, oily ingredients, and surfactants below 60°C during the solution preparation process, and to impregnate the fiber web at a temperature below 60°C during the solution impregnation process, in conjunction with the starch. More preferably, both the solution preparation and impregnation processes are conducted at temperatures below 50°C, and more preferably below 45°C.
[0039] The pharmaceutical solution preparation process and the pharmaceutical solution impregnation process in the manufacturing method of the present invention are as follows.
[0040] (1) Drug preparation process
[0041] The solution used to impregnate the fiber web includes the aforementioned moisturizing ingredients, water, oily ingredients, and plant-based powders as essential components. It may also include surfactants as needed, but does not include adhesives such as sodium carboxymethyl cellulose, polyvinyl alcohol, water-soluble polyurethane resin, latex, or starch paste obtained by gelatinizing starch at a temperature above 60°C to bond the plant-based powders to the fiber webs and prevent them from falling off.
[0042] The preparation of the solution is as follows: A surfactant is added to the oily components as needed and heated and mixed. Water and moisturizing ingredients are then added to prepare an oil-in-water emulsion. Next, plant-based powder is added while stirring to form a suspension. It should be noted that, as mentioned above, when starch is used as the plant-based powder, the process is carried out at a temperature below 60°C.
[0043] Furthermore, the preferred ratio of moisturizing components, water, oily components, and plant-based powders in the medicinal solution at 23°C and 50% relative humidity is 1:0.05~1.0:0.01~1.0:0.01~1.0, and more preferably 1:0.1~0.5:0.03~0.5:0.03~0.5.
[0044] (2) Drug solution immersion process
[0045] As a method for impregnating the fiber web with the solution prepared as described above, in addition to spraying the solution using a spraying device (sprayer spraying), the solution can also be coated using a printing roller (roller coating), etc.
[0046] The preferred impregnation rate of the solution on the fiber web is 1–60% by weight. When the impregnation rate is less than 1% by weight, the improvement in skin feel is minimal; when it exceeds 60% by weight, the strength decreases, and the improvement in skin feel does not increase further. Therefore, setting the impregnation rate of the solution to 1–60% by weight presents no practical obstacle, but the preferred content for improving skin feel and achieving a balance between skin feel and strength is 10–50% by weight, more preferably 20–40% by weight.
[0047] [Invention Effects]
[0048] According to the present invention, a fiber web product can be provided that, by setting the type of pulp fiber, the amount of moisturizing component, moisture, oil component, and plant-based powder in combination with the pharmaceutical solution within a specific range, exhibits excellent skin-touch properties such as smooth fuzziness, softness, moisture, and non-stickiness on the surface of the fiber web, and generates less dust such as powder and pulp fiber without the addition of adhesive components. Furthermore, a fiber web product that retains sufficient strength and has excellent practicality, making it ideal for hygiene and household applications, can be obtained.
[0049] Furthermore, by simply impregnating the fiber web with a solution containing dispersed powder, the hydrogen bonds between the pulp fibers are eased by the moisturizing and oily components in the solution, allowing the powder particles to intervene between the pulp fibers and naturally generate fuzz. Therefore, a fuzz-generating process is unnecessary, as is the use of special machinery or devices, which involves a physical method of forcibly peeling and pulling out a portion of the fibers by pressing protrusions onto the surface of the fiber web. Attached Figure Description
[0050] [ Figure 1 [Image (photograph) showing the fuzzy state of pulp fibers]
[0051] [ Figure 2 [Illustrative diagram of the sample used for determining the number of napping fibers]
[0052] [ Figure 3 A cross-sectional view of the inspection material in a conceptual manner, representing the state of the fuzzy texture.
[0053] [ Figure 4 A diagram illustrating the method for determining the number of dust particles.
[0054] [ Figure 5 A diagram illustrating the method for determining the number of dust particles. Detailed Implementation
[0055] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings.
[0056] Table 1 shows the component combinations and various evaluation results in the embodiments that embody the present invention, and Table 2 shows the component combinations and various evaluation results in the comparative examples.
[0057]
[0058]
[0059] Examples 1 to 9 in Table 1 are examples in which the pulp blending ratio, the type and amount of oily components in the solution, and the type of plant-based powder were changed.
[0060] Furthermore, in Comparative Examples 1 and 2 of Table 2, mineral powders were added to the pharmaceutical solution; in Comparative Example 3, no oily components and surfactants were added; in Comparative Example 4, no powders were added; in Comparative Example 5, the fiber web was only coniferous pulp; and in Comparative Examples 6 and 7, the fiber web base paper was not impregnated with the pharmaceutical solution.
[0061] The papermaking method and chemical impregnation method for fiber webs are as follows.
[0062] Unbeaten NBKP (coniferous kraft bleached pulp: weight-weighted average fiber length 2.4–2.6 mm, fiber coarseness 0.148 mg / m) pulp was beaten to achieve a Canadian standard water content reduction of 40–60 ml. Additionally, LBKP (broadleaf kraft bleached pulp: weight-weighted average fiber length 0.60–0.72 mm, fiber coarseness 0.057 mg / m) pulp was beaten to achieve a Canadian standard water content reduction of 30–40 ml.
[0063] Next, the pulp was mixed to achieve the pulp blending ratios shown in Tables 1 and 2, with 0.2% by weight of wet strength agent added per unit of pulp based on solids content. Then, the dry crepe paper was formed using a paper machine according to conventional methods.
[0064] The resulting crepe paper weighed 15g / m². 2 With a crepe rate of 24%, two pieces of this crepe paper are overlapped and rolled into a roll.
[0065] Next, the solution prepared by mixing the components shown in Tables 1 and 2 is continuously sprayed from both sides of two overlapping sheets of base paper at a rate of 25% by weight per crepe, and then rolled into a roll again. The rolled crepe paper is then left to stand at room temperature for at least 24 hours to allow the solution to evenly impregnate the entire fiber fabric.
[0066] Next, with the crepe paper facing forward, two overlapping sheets of raw paper were cut into dimensions of 200 mm longitudinally (in the papermaking direction) and 225 mm transversely (in the papermaking width direction) to prepare multiple samples.
[0067] Furthermore, each sample was left to stand for more than 24 hours at a temperature of 23±5℃ and a humidity of 50±5% before undergoing the following functional tests (skin tactile test) and physical property tests for evaluation.
[0068] A. Sensory testing (skin tactile test)
[0069] Ten reviewers touched each sample by hand and evaluated their feel according to the following criteria (smooth fuzziness, softness, moisture, and non-stickiness).
[0070] Specifically, for smoothness, softness, and moisture, "excellent" was rated 3 points, "excellent" was rated 2 points, "slightly excellent" was rated 1 point, and "not excellent" was rated 0 points. The scores given by the 10 reviewers are ranked as follows.
[0071] "26-30 points": ◎
[0072] "16-25 points": ○
[0073] "6-15 points": △
[0074] "0-5 points": ×
[0075] According to the ranking, ◎ is the best and × is the worst.
[0076] For stickiness based on oily components, the following criteria are used for evaluation.
[0077] That is, "feeling a strong stickiness" is scored as 3 points, "feeling stickiness" as 2 points, "feeling a slight stickiness" as 1 point, and "not feeling stickiness" as 0 points. The scores given by the 10 commentators are ranked as follows.
[0078] "26-30 points": ×
[0079] "16-25 points": △
[0080] "6-15 points": ○
[0081] "0-5 points": ◎
[0082] According to the sorting, × is the stickiest and ◎ is the least sticky.
[0083] B. Physical property test
[0084] (1) Determination of the number of napping fibers (nailing degree)
[0085] A single pulp fiber that protrudes from the surface of the fiber web—that is, a pulp fiber in which one end of the fiber's length is located inside the fiber web and the other end stands upright from the surface of the fiber web—is defined as a pile fiber. In this test, the number of pile fibers that protrude from the surface of the fiber web at a height of 0.1 mm or more is counted.
[0086] Figure 1 It is a diagram (photograph) showing the fuzzy state of pulp fibers. Figure 1The number of raised fibers (raised fiber count) marked with arrow A is relatively large, and when the raised fibers are soft, they exhibit a smooth, skin-like feel with a sense of thickness. The number of raised fibers protruding from the surface of the fiber web at a height of 0.1 mm or more is preferably 400 or more, more preferably 500 or more, and even more preferably 600 or more, under the following measurement conditions.
[0087] The specific method for determining the number of napped fibers is as follows.
[0088] like Figure 2 As indicated, along the fold line 11 that intersects at a 45-degree angle relative to the paper-making direction B, two overlapping samples 10 are arranged as shown. Figure 3 The examination material 24 is prepared by sandwiching and bending a glass slide 21 in the middle, and then sandwiching it from both sides with other glass slides 22 and 23.
[0089] The aforementioned inspection material 24 is placed on a horizontal movable stage under a microscope, and the fuzzy state of the end of the inspection material 24 is observed from direction C, which is orthogonal to the slides 21-23.
[0090] From the protruding fibers at the end of the test material 24, the number of fibers 12 with a height of 0.1 mm or more is counted within a 2.5 mm length spanning the sample 10 in the field of view of the microscope.
[0091] The measurement position on sample 10 was changed, and 40 measurements including the above series of procedures were performed and totaled to determine the number of pile fibers 12 per 100 mm length of sample 10.
[0092] It should be noted that slides 21-23 are 1.3 mm thick, 76 mm long, and 26 mm wide, and the magnification of the microscope is set to 40x.
[0093] Regarding the measurement range of sample 10 in this determination, the length direction (L) is 100 mm, and the width direction (W) is 1.6 mm, which is the sum of the thickness of the glass slide 21 (1.3 mm) and the thickness of sample 10 (0.15 mm × 2). Therefore, the measurement area (S) is 160 mm² according to S = L × W. 2 .
[0094] Figure 3 The diagram shows the case where two samples 10 are overlapped, but the sample can be one piece or more than three pieces. Furthermore, the width (W) of the measurement range varies depending on the thickness of the sample 10, and the measurement area (S) also changes accordingly, but the number of napping fibers is converted to 160 mm² by the measurement area (S). 2 And find out.
[0095] (2) Determination of dust particle number
[0096] The powder and pulp fibers that fall off when the fiber web is subjected to mechanical impact are defined as dust, and the number of particles is measured by a particle number measuring device.
[0097] It should be noted that the preferred dust particle count is per 1800 cm² of the fiber web surface area. 2 The number is less than 6,000, more preferably less than 5,000, and even more preferably less than 4,000.
[0098] As a specific measurement method, 40 measurements were performed, including a series of procedures as described below, to determine the average number of dust particles.
[0099] First, such as Figure 4 As indicated, sample 10 is placed in a zippered plastic bag 30 and sealed with air. The plastic bag 30 is then placed on the horizontal rotation axis 40 of the rotating device and rotated at a speed of 25 times per minute for 10 minutes. As a result, the sample 10, falling in any direction (mainly the radial direction of the rotation path), is impacted inside the plastic bag 30, causing dust particles to detach from the sample 10.
[0100] Next, as Figure 5 In this way, the number of dust particles present inside the plastic bag 30 is measured by the particle count measuring device 50, and the number of dust particles generated and detached from the sample 10 is counted by subtracting the value of the blank experiment (the number of dust particles inside the plastic bag 30 in the state where the sample 10 is not sealed) from the measured value.
[0101] The measurement conditions are as follows.
[0102] • Rotating device: SCROLLER SCR-120 (manufactured by Seieido Inouchi)
[0103] • Plastic bag: 240mm wide × 340mm deep × 0.04mm thick, capacity 4.0L
[0104] • The measured particle size of the dust is ≥5μm.
[0105] • Particle number measuring device: PARTICLE MONITOR GT-32 (made by Shibata Scientific)
[0106] • Measurement time: 60 seconds
[0107] • Air intake rate based on particle number measurement device: 2.83 L / min
[0108] • The dimensions of the samples used in this measurement were: 200mm in length × 225mm in width, with two samples overlapping.
[0109] • Surface area: 200mm × 225mm × 4 (two overlapping surfaces) = 1800cm² 2
[0110] It should be noted that the surface area varies depending on the size of the sample, but the dust count is converted to a surface area of 1800 cm². 2 And find out.
[0111] (3) Strength test
[0112] Based on JIS S3104 (facial tissue), the tensile strength of the fiber web in the longitudinal direction (papermaking direction) during drying was measured 10 times, and its average value was calculated.
[0113] C. Evaluation
[0114] Based on the results of the above experiments, the following evaluation can be made.
[0115] (1) Example
[0116] In Examples 1 to 4 in Table 1, only the pulp blending ratio was changed, while the drug composition and drug impregnation rate remained the same.
[0117] According to Examples 1-4, as the blending rate of hardwood pulp gradually increases, the softness, fuzz count, and dust count also increase. This is believed to be because, compared to softwood pulp, hardwood pulp has shorter and finer fibers, resulting in narrower hydrogen bond points and areas between pulp fibers, making the sheet structure more prone to loosening in the presence of the chemical solution. Furthermore, a higher blending rate of hardwood pulp leads to a greater absolute number of pulp fibers, thus increasing the fuzz count.
[0118] Example 5 is an example in which the amount of powder in Example 4 is increased. Compared with Example 4, the number of fuzzy fibers increases, which is attributed to the increased amount of powder.
[0119] Example 6 is an example where the amount of oily component was reduced compared to Example 5, and the number of dust particles increased compared to Example 5. This is believed to be because the adhesive effect of the dust particles based on the oily component was reduced.
[0120] Example 7 is an example in which the type of oily component in Example 3 was changed, and the evaluation results were substantially the same as those in Example 3.
[0121] Example 8 is an example of an oily component containing solids. Compared with Examples 3 and 7, it was observed to be slightly sticky and less soft.
[0122] Example 9 is an example in which the type of powder was changed compared to Example 3, and the softness was slightly reduced compared to Examples 3 and 7.
[0123] (2) Comparative Examples
[0124] In Comparative Examples 1 and 2 in Table 2, the powders were changed from plant-based powders to mineral powders, namely talc and kaolin, and the number of dust particles was much larger than in Examples 1 to 9.
[0125] This is believed to be because: talc and kaolin particles are plate-shaped crystals, which are easy to peel off and easily fall off from the fiber fabric and scatter into dust. Furthermore, due to the small average particle size of the powder, the number of powder particles per unit weight is large, thus reducing the effect of preventing the agent from falling off.
[0126] Furthermore, in Comparative Examples 1 and 2, the evaluation of smooth fuzziness also decreased. This is believed to be because: due to the smaller average particle size of the powder, the smoothness is higher, but the powder does not contribute to the smooth fuzziness that is accompanied by a sense of thickness.
[0127] Comparative Example 3 is an example from Example 3 where the oily component has been removed, and the number of dust particles is much higher than in Example 3. Based on this result, by including the oily component in the agent, dust can be effectively suppressed.
[0128] In Comparative Example 4, the sample from Example 2 was made without the powder. In this Comparative Example 4, the stickiness caused by the oily components was felt due to the absence of powder, and the number of fuzzy fibers was reduced, resulting in a lower evaluation of the fuzziness.
[0129] In Comparative Example 5, the pulp fibers consisted only of softwood pulp and not hardwood pulp, resulting in a lower number of fuzzy fibers. It should be noted that the number of dust particles was the lowest among the comparative examples.
[0130] Coniferous pulp, due to its long and coarse fibers, exhibits stronger hydrogen bonds between fibers, making it less prone to pulp liquefaction and fuzzing even in the presence of chemicals. Furthermore, compared to hardwood pulp, it has fewer fibers per unit area, resulting in fewer fuzzing fibers. Additionally, compared to the size of the pulp fibers, the average particle size of the powder is smaller, resulting in a less tactile feel and a sticky sensation based on its oily components.
[0131] In Comparative Examples 6 and 7, the original paper was not impregnated with the chemical solution.
[0132] Comparative Example 6 and Example 2 had the same pulp blending ratio, but Example 2, which contained powder from the pharmaceutical solution, had a higher number of fuzzy fibers and suppressed the generation of dust particles. In other words, as in the examples including Example 2, by impregnating the fiber web with a given blend of a pharmaceutical solution containing moisturizing ingredients, water, oily ingredients, and plant-based powders, it is possible to effectively produce fuzzy fibers with a thick feel, and the shedding of pulp fibers and powders is suppressed.
[0133] (3) Summary
[0134] In each embodiment, the fuzzing of the pulp fibers is generated by the mitigation of hydrogen bonds between pulp fibers brought about by moisturizing and oily components, and by the intervention of powder (starch) between pulp fibers. Therefore, unlike the fuzzing that is forcibly formed by mechanical force in the prior art, it is a naturally occurring fuzzing state.
[0135] Compared to pulp fibers, when the powder particles are too small, they cause the pulp fibers to separate from each other, thus reducing the effect of promoting fuzzing. When the powder particles are too large, the powder separates from the pulp fibers and falls off as dust. Therefore, the average particle size of the powder is set, for example, to 2 to 50 μm, preferably to 5 to 30 μm, to generate suitable fuzzing. On the other hand, combined with the adhesiveness based on the oily components, the generation and shedding of dust can be suppressed.
[0136] In addition, the fuzzy pulp fibers are plasticized by moisturizing ingredients and smoothed by oily ingredients, giving them an extremely soft feel when in contact with the skin.
[0137] Although the various embodiments contain oily ingredients, they do not feel overly sticky.
[0138] Compared to starch, oily components are more easily absorbed by pulp fibers, which have a higher affinity for oil. Therefore, when the fiber web comes into contact with human skin, it exhibits a smooth, non-sticky feel by simultaneously experiencing the oily sensation of pulp fibers and the non-oily sensation of starch.
[0139] In contrast, it is believed that, for example, in the case of coniferous pulp in Comparative Example 5, where the fiber size is much larger than the starch particle size, when touching the surface of the fiber web, there is less contact with starch, and the oily feel of the pulp fibers is strongly felt, thus increasing the stickiness.
[0140] In each embodiment, the introduction of starch between pulp fibers poses a risk of reduced paper strength, but no significant reduction in strength has been observed. This is believed to be because the pulp fibers are hydrogen-bonded through the starch.
[0141] The hydrogen bonds between pulp fibers are not soft bonds. However, in the bonding of pulp fibers separated by starch, the starch itself is plasticized by moisturizing components and water, becoming a flexible bond with mobility. As a result, the soft feel of the fiber web can be maintained, and the reduction in strength can be inhibited.
[0142] [Industrial Applicability]
[0143] The fiber web product of the present invention has a smooth and thick nap, a soft and moist skin feel, less dust generation and shedding, and sufficient strength.
[0144] Therefore, it is very useful as a fiber web product for hygiene and household use, such as facial tissues, toilet paper, and paper towels.
[0145] [Symbol Explanation]
[0146] 10: Sample
[0147] 11: Folded line
[0148] 12: Bundled fibers
[0149] 21-23: Glass slides
[0150] 24: Check the materials
[0151] 30: Plastic bags
[0152] 40: Rotation axis
[0153] 50: Particle number measuring device
Claims
1. A fiber web product impregnated with a medicinal solution in a fiber web comprising hardwood pulp, said medicinal solution comprising a moisturizing component, water, an oily component, and a plant-based powder comprising starch. The plant-based powder has an average particle size of 5~30μm. The fiber web contains more than 50% by weight of hardwood pulp. The ratio of the moisturizing component, the water, the oily component, and the plant-based powder in the medicinal solution at 23℃ and 50% relative humidity is 1:0.05~1.0:0.01~1.0:0.01~1.
0.
2. The fiber web product according to claim 1, wherein, The fiber web is dry crepe paper.
3. The fiber web product according to claim 1 or 2, wherein, The moisturizing ingredient includes glycerol.
4. The fiber web product according to claim 1 or 2, wherein, The oily component contains hydrocarbons.
5. The fiber web product according to claim 1 or 2, wherein, The starch is corn starch.
6. The fiber web product according to claim 1 or 2, wherein, The plant-based powder is introduced between the pulp fibers of the fiber web, where the hydrogen bonds have been neutralized by the moisturizing and oily components, causing the pulp fibers to become fuzzy.
7. The fiber web product according to claim 6, wherein, per 160 mm² of the fiber web surface area 2 In this process, the number of pulp fibers protruding from the surface of the fiber web at a height of 0.1 mm or more and thus creating a nap is 400 or more.
8. The fiber web product according to claim 6, wherein, per 1800 cm² of the fiber web surface area 2 In this case, the number of dust particles that are generated from the fiber web and fall off as dust containing the plant-based powder or the pulp fiber is 6,000 or less.
9. A method for manufacturing a fiber web product, wherein, A solution containing moisturizing ingredients, water, oily components, starch-containing plant-based powders, and surfactants is prepared, and the solution is sprayed or rolled onto fiber webs containing hardwood pulp and impregnated. The plant-based powder has an average particle size of 5~30μm. The fiber web contains more than 50% by weight of hardwood pulp. The ratio of the moisturizing component, the water, the oily component, and the plant-based powder in the medicinal solution at 23℃ and 50% relative humidity is 1:0.05~1.0:0.01~1.0:0.01~1.
0.
10. The method for manufacturing fiber web products according to claim 9, wherein, The medicinal solution is prepared by keeping the temperature of the emulsion containing the moisturizing ingredients, the moisture, the oily ingredients and the surfactant below 60°C, and by combining it with starch as the plant-based powder, so that the medicinal solution impregnates the fiber fabric at a temperature below 60°C.
Citation Information
Patent Citations
Fiber web having high water retention and production thereof
JP1993156596A
Fiber web product and its production
JP2001011790A
Sanitary tissue paper and method for producing sanitary tissue paper
JP2003342899A
Chemical-containing tissue paper
JP2007204868A
Liquid chemical including tissue paper
JP2008080027A